THE EFFECT OF STRIP STORY MEDIA ON STUDENTS' LEARNING OUTCOMES - Nasution, Amanda Sari; Hanida, Rahmi Seri; Hanifah Oktarina (Esteem Journal of English Education Study Programme, 2025)
Effective communication between teachers and students plays a crucial role in the success of the learning process. Poor communication can hinder the delivery of material, making the learning process less engaging. One method to enhance learning engagement is through the use of strip story media. This medium is practical, simple, and enjoyable, supporting both teachers and students in creating a dynamic learning environment. This study aims to investigate the effect of using strip story media on students' learning outcomes in social studies. The research employed a one-group pretest-posttest experimental design. The results showed that the average score of students using strip story media was 80, higher than the control group's average score of 95. Statistical analysis using the Independent Sample t-Test indicated a significant effect, with the calculated t-value (t_calculated = 9.149) exceeding the critical t-value (t_table = 2.564) and a significance level (Sig = 0.000) below 0.05. This led to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha), confirming that strip story media significantly impacts the social studies learning outcomes of fourth-grade students at SD Negeri 080 Panyabungan. In conclusion, strip story media positively and significantly affects students' learning outcomes. The findings imply the need for integrating innovative teaching media like strip stories to enhance learning. Future research could explore its application in other subjects or educational levels to expand its benefits.